Kepemimpinan Kepala Desa dalam Pembangunan Bidang Infrastruktur di Desa Pantai Kecamatan Kapuas Barat - Fitriani Fitriani; Mita Sari; Putri Irianti Sintaman (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
The village chief as the leader who is directly elected by the villagers and it is believed and also claimed to have good leadership for the development of rural infrastructure as well as to invite the community to participate in the advancement of the village. An organization will succeed or fail is determined by the leadership. This study raises the issue: (1) How is the leadership of the village chief in the construction of infrastructure in the coastal village? (2) What are the factors that affect the leadership of the village chief in the construction of infrastructure in the coastal village? The method used is a qualitative research method with a descriptive approach. The data used is primary data (observations and interviews) and secondary data (literature). The primary data sources are direct observation, interviews and recording the data in the seaside village office. Then, it is analyzed with related theories. The conclusion of this research was the leadership of the village chief in developing of infrastructure field in Pantai village, west Kapuas subdistrict, Kapuas district. It is known by the head chief’s way to.